2021
DOI: 10.1371/journal.pntd.0009987
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of cortisol are associated with the severity of experimental visceral leishmaniasis in a Leishmania (L.) infantum-hamster model

Abstract: Background Several infectious diseases are associated with hypothalamic-pituitary-adrenal (HPA) axis disorders by elevating circulating glucocorticoids (GCs), which are known to have an immunosuppressive potential. We conducted this study in golden hamsters, a suitable model human visceral leishmaniasis (VL), to investigate the relationship of Leishmania (L.) infantum infection on cortisol production and VL severity. Methods L. infantum-infected (n = 42) and uninfected hamsters (n = 30) were followed-up at 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Following this result, Barros‐Goncalves et al. (2021) found that cortisol level is associated with the severity of infection.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Following this result, Barros‐Goncalves et al. (2021) found that cortisol level is associated with the severity of infection.…”
Section: Discussionmentioning
confidence: 73%
“…Virulence genes did not significantly affect cortisol levels in acute infection, while it does after 6 days; this could be due to the overexpression of virulence factors throughout the disease course. Following this result, Barros-Goncalves et al (2021) found that cortisol level is associated with the severity of infection.…”
Section: Ta B L E 4 Virulence Genes Profile Of the Recovered Aeromona...mentioning
confidence: 73%
“…Virulence genes did not significantly affect cortisol levels in acute infection while it does after six days; this could be due to the overexpression of virulence factors throughout the disease course. Following this result, Barros-Goncalves et al (2021) found that cortisol level is associated with the severity of infection.…”
Section: Oreochromis Niloticusmentioning
confidence: 73%
“…For example, in case of African Trypanosomes HAT patients display higher serum levels of cortisol as compared to controls, probably reflecting a stress response to the ongoing inflammation ( 141 , 142 ). Similarly, modulations of cortisol levels and GC synthesis were documented to occur during experimental Leishmaniasis and Chagas disease ( 143 145 ). More recently SARS-Cov-2 infection was suggested to affect GC synthesis since cortisol levels were found to be lower in critically ill patients with COVID-19 as compared to those of non-COVID-19 critically ill patients.…”
Section: The Mif/glucocorticoid Dyadmentioning
confidence: 89%